2014
DOI: 10.1073/pnas.1322264111
|View full text |Cite
|
Sign up to set email alerts
|

O-Glycosylation regulates polarized secretion by modulating Tango1 stability

Abstract: Polarized secretion is crucial in many tissues. The conserved protein modification, O-glycosylation, plays a role in regulating secretion. However, the mechanisms by which this occurs are unknown. Here, we demonstrate that an O-glycosyltransferase functions as a novel regulator of secretion and secretory vesicle formation in vivo by glycosylating the essential Golgi/endoplasmic reticulum protein, Tango1 (Transport and Golgi organization 1), and conferring protection from furin-mediated proteolysis. Loss of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 39 publications
(58 reference statements)
4
58
0
Order By: Relevance
“…At the Drosophila NMJ, a similar reciprocal suppression interaction between pgant glycosyltransferases involved in O-linked glycosylation regulates synaptogenesis via integrin-tenascin transsynaptic signaling (Dani et al, 2014). A recent study reported that pgant activity protects substrates from Furin-mediated proteolysis, which is a protease responsible for processing or activating Drosophila Mmp1 and Mmp2 (Zhang et al, 2014). Thus, Mmp proteolytic and glycan mechanisms could converge within the NMJ synaptomatrix to regulate trans-synaptic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…At the Drosophila NMJ, a similar reciprocal suppression interaction between pgant glycosyltransferases involved in O-linked glycosylation regulates synaptogenesis via integrin-tenascin transsynaptic signaling (Dani et al, 2014). A recent study reported that pgant activity protects substrates from Furin-mediated proteolysis, which is a protease responsible for processing or activating Drosophila Mmp1 and Mmp2 (Zhang et al, 2014). Thus, Mmp proteolytic and glycan mechanisms could converge within the NMJ synaptomatrix to regulate trans-synaptic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, proximity to endoplasmic reticulum/Golgi trafficking signals is notable because O-glycosylation has been demonstrated to regulate secretion, suggesting a function in vesicular transport. [69][70][71] Given that vesicular trafficking signals remain poorly annotated, it will be of interest to further investigate the potential role of O-glycosylation in protein trafficking experimentally.…”
mentioning
confidence: 99%
“…GalNAc-T6 is one of the 20 family members in mammals that are responsible for the initiation of O-linked glycosylation (2). Members of this family are essential in Drosophila and are involved in various cellular and developmental processes (6,7). Aberrant GALNT6 expression has previously been observed in several cancer types, but the biological role of GALNT6 in vivo is still unknown.…”
mentioning
confidence: 99%
“…These cells (also known as SimpleCells or LS174T SC ) were compared with a version with GALNT6 ablated (LS174T SC ⌬T6) to identify the proteins that are specifically glycosylated by GalNAc-T6. Interestingly, they found a small number of proteins that appear to be GalNAc-T6 -specific targets, including MIA3 (also known as Tango1), which had previously been associated with colon cancer development (8) and is essential for secretory apparatus structure and secretion (7,9).…”
mentioning
confidence: 99%